2012
DOI: 10.1002/pits.21631
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of class‐wide taped problems and cover, copy, and compare for enhancing mathematics fluency

Abstract: An adapted alternating treatments design was used to compare the effects of class‐wide applications of Taped Problems (TP) and Cover, Copy, and Compare (CCC) procedures designed to enhance subtraction fact fluency in an intact third‐grade classroom. During the TP procedure, a tape provided an auditory prompt (i.e., the problem), followed by a 2‐second delay and then the correct answer. Students attempted to supply the correct answer before the answer was provided by the tape. During the CCC procedure, students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 28 publications
(26 reference statements)
1
22
0
Order By: Relevance
“…The results of this investigation enhance the TP research by corroborating previous investigations that showed a constant 2-s delay results in increased outcomes (Poncy et al, 2012) and demonstrating that using a nodelay procedure is effective as well. However, it is important to note that all students in the present study could accurately complete the targeted problems and that the effect of reducing, or eliminating, a wait time to respond may have a different outcome when attempting to promote accurate responding.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of this investigation enhance the TP research by corroborating previous investigations that showed a constant 2-s delay results in increased outcomes (Poncy et al, 2012) and demonstrating that using a nodelay procedure is effective as well. However, it is important to note that all students in the present study could accurately complete the targeted problems and that the effect of reducing, or eliminating, a wait time to respond may have a different outcome when attempting to promote accurate responding.…”
Section: Discussionsupporting
confidence: 91%
“…Previous TP interventions demonstrated that varying time delays (McCallum et al, 2006;Miller, Skinner, Gibby, Galyon, & Meadows-Allen, 2011) and constant time delays (Poncy et al, 2007;Poncy et al, 2012) can be effective, but researchers had yet to examine and compare the relative effectiveness of different time delay procedures. In the present study, when analyzing the data by session both no delay and 2-s delay conditions resulted in improvements in math fact automaticity in a second-grade general education class.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on the research results of this and other studies, it can be concluded that the TP interventions help students perform math facts fast enough that they do not need to use finger counting strategies. It was also concluded that TP interventions are efficient in the development of fluency in basic math skills in other studies which has different number and characteristics of participants and whose intervention forms were designed in different conditions (Aspiranti et al, 2011;Cressey and Ezbicki, 2017;McCallum et al, 2006;Miller et al, 2011;Mong and Mong, 2010;Poncy et al, 2012;Uysal, 2017;Windingsstad et al, 2009). Then, TP can be considered as a method that can be applied to all students as a group or individually in different educational settings.…”
Section: Discussionmentioning
confidence: 94%
“…However, the issue of measurement precision extends to the use of such probes within a research context and to progress monitoring as well. Numerous repeated-measures group- and single-subject design studies have evaluated remedial strategies to improve accuracy and fluency in whole-number operations and have used SSM-CBM as a primary or sole outcome measure (e.g., Codding et al, 2007; Hawkins et al, 2009; Poncy et al, 2012).…”
Section: Precision Of Slope For Ssm-cbmsmentioning
confidence: 99%